Expression of immune genes in systemic and mucosal immune tissues of channel catfish vaccinated with live theronts of Ichthyophthirius multifiliis. Issue 66 (July 2017) - Xu, De-Hai; Moreira, Gabriel S.A.; Shoemaker, Craig A.; Zhang, Dunhua; Beck, Benjamin H.
Abstract: Ichthyophthiriasis caused by Ichthyophthirius multifiliis (Ich) has a worldwide distribution and affects most freshwater fishes. Fish surviving natural infection and/or immunized with Ich develop strong innate and adaptive immune responses. However, there is a lack of the knowledge regarding immune gene expression patterns in systemic and mucosal immune tissues, and how immune genes interact and lead to innate and adaptive immune protection against Ich infection in fish. The objective of this study was to investigate the expression of innate and adaptive immune-related genes in systemic (liver, spleen) and mucosal (gill, intestine) tissues of channel catfish over time following vaccination with live Ich theronts. The vaccinated fish showed significantly higher antibody titers and survival (95%) than those of mock immunized fish. Expression of IgM and IgD heavy chain genes exhibited a rapid increase from 4 h (h4) to 2 days (d2) post-vaccination in systemic immune tissues. Immune cell receptor genes (CD4, CD8-α, MHC I, MHC II β, TcR-α, and TcR-β) were more highly upregulated and remained upregulated for longer duration in systemic tissues than in mucosal tissues of the vaccinated fish. The cytokine genes IL-1βa and IFN-γ were rapidly upregulated in both systemic and mucosal tissues of vaccinated fish, with peak expression from h4 to d1 post-vaccination. Toll-like receptor genes TLR-1 and TLR-9 showed relatively stable upregulation in the gill of immunized fish following vaccination. Results of this study revealed the molecular immune responses in mucosal and systemic tissues of vaccinated fish and demonstrated that Ich vaccination resulted in innate and adaptive immune responses against Ich infection. Highlights: Evaluated molecular responses in mucosal and systemic immune tissues of catfish. Vaccinated fish showed higher anti-Ich antibody level and survival than control fish. Expression of Immunoglobulin genes increased rapidly from h4 to d2 post vaccination. Cell receptor genes are more upregulated in systemic tissues than in mucosal tissues. Vaccination resulted in innate and adaptive immune responses against Ich infection.